UNIDO forging ahead : milestones achieved 2006 - 2007 (UNIDO ViennaAT, 2007)
Considers significant milestones such as consolidating and deepening the reform process, enhancing programmes through continuity, quality and growth; advancing UN reform and building strategic partnerships; and, increasing visibility.
Keywords: UNIDO